Gastrointestinal endoscopy in the cancer patient - Deutsch, John C.; Banks, Matthew R. (Wiley-Blackwell, 2013)
This book is a full colour, highly clinical multi-media atlas focusing on the role diagnostic and therapeutic endoscopy plays in the management of patients with cancer. Conveniently split into sections for each part of the GI tract, each section will follow a consistent structure. With 400 high-quality images and in addition, 21 high-definition videos showing endoscopy from the experts, this book is the perfect consultation and learning tool for all gastroenterologists, endoscopists, GI surgeons and oncologists.